Specimen collection is essential for modern science. - Michael W Nachman; Elizabeth J Beckman; Rauri Ck Bowie; Carla Cicero; Chris J Conroy; Robert Dudley; Tyrone B Hayes; Michelle S Koo; Eileen A Lacey; Christopher H Martin; Jimmy A McGuire; James L Patton; et al. (PLoS Biology, 2023)
Natural history museums are vital repositories of specimens, samples and data that inform about the natural world; this Formal Comment revisits a Perspective that advocated for the adoption of compassionate collection practices, querying whether it will ever be possible to completely do away with whole animal specimen collection.